Surprise court ruling: Jokowi's omnibus law hits snag - Borsuk, Richard (2022)
November’s decision by an Indonesian court to declare President Joko Widodo’s Omnibus Law “conditionally unconstitutional” due to procedural flaws has put an unexpected twist to his agenda for 2022. Amendments needed by 2023 should be passed by parliament, but there is no guarantee the path will be smooth.